In defense of sugar: a critical analysis of rhetorical strategies used in The Sugar Association's award-winning 1976 public relations campaign - Cristin E. Kearns; Stanton A. Glantz; Dorie E. Apollonio (BMC, 2019)
Abstract Background In 1976, the U.S. Sugar Association (SA), a globally networked trade organization representing the cane and beet sugar industry, won the Public Relations Society of America's (PRSA) Silver Anvil Award for a crisis communication campaign. Their campaign successfully limited the diffusion of sugar restriction policies to control obesity, heart disease, diabetes, and dental caries, and marked the beginning of the modern-day SA. The sugar industry continues to resist measures to reduce sugar consumption, therefore understanding and addressing industry opposition is crucial to achieving global targets to reduce non-communicable disease. Methods We critically analyze common crisis management rhetorical strategies used by SA to defend itself from perceived wrongdoing, and sugar from perceptions of harm using a thematic content analysis based on Hearit's Corporate Apologia theory. Data sources were internal SA documents related to the 1976 Silver Anvil Award in 1) PRSA records, 2) Great Western Sugar Company records, and 3) William Jefferson Darby Papers. Results SA, using prototypical apologia stances (counterattack, differentiation, apology, and corrective action) and rhetorical dissociation strategies (appearance/reality, opinion/knowledge, and act/essence) constructed a persuasive narrative to successfully defend sugar from a product safety crisis, and the sugar industry from a social legitimacy crisis. SA's overarching narrative was that restricting sugar, which it claimed was a valuable food that makes healthy foods more palatable, would cause harm and that claims to the contrary were made by opportunists, pseudoscientists, food-faddists, lay nutritionists or those who had been misled by them. SA's apologia does not meet criteria for truthfulness or sincerity. Conclusion Corporate apologia theory provides an accessible way of understanding sugar industry crisis communication strategies. It enables public health actors to recognize and predict industry corporate apologia in response to ongoing product safety and social legitimacy challenges. Industry counterarguments can be examined for truthfulness and sincerity (or the lack thereof), and explained to policymakers considering sugar restriction policies, and to the public, thereby decreasing the effectiveness of illegitimate industry communication efforts to oppose regulation and legislation.